Penegakan Hukum Pelanggaran Pemilihan Umum Yang Bersifat Terstruktur, Sistematis dan Masif - Asnawi Asnawi; Asih Gaduh Andriani; Ayang Fristia Maulana (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Elections are the embodiment of a democratic state to elect leaders democratically. The inclusion of material is structurally, systematically and massively violated in statutory regulations, the authority to resolve which is given to the General Election Supervisory Agancy, is a new breakthrough. Identification of problems in this study, namely: first, how is the law enforcement system; second, how effective it is in handling law enforcement against general election violations. The research conducted is normative juridical law research with a legal approach, based on literature which uses library materials as basic data. This study uses aditional data supported by main data in the form of structured interviews. The aditional data used consists of main legal sources, secondary legal sources and tertiary legal sources. The approach in this study uses a statutory research approach and a case approach, concepts that are directed at analyzing a hierarchical regulation, concept, theory and doctrine in it. Whereas the research results obtained: first, the law enforcement of TSM violations uses the election administration law enforcement system. With severe formal and material requirements and the resulting decision is not final; second, that TSM violation law enforcement is not effective in being able to reach the violations that have occurred. Of the 4 (four) reports of suspected TSM violations that were received, 1 (one) report was not registered and 3 (three) other reports were not received at the preliminary hearing